Twelve-year global publications on small incision lenticule extraction: A bibliometric analysis - Han, Tian; Zhao, Liang; Shen, Yang; Chen, Zhi; Yang, Dong; Zhang, Jiaoyan; Sekundo, Walter; Shah, Rupal; Tian, Jinhui; Zhou, Xingtao (Frontiers in Medicine, 2022)
PPurpose: To analyze the development process of small incision lenticule extraction (SMILE) surgery in a 12-year period. Methods: We conducted a literature search for SMILE research from 2011 to 2022 using the Science Citation Index Expanded (SCIE) of the Web of Science Core Collection (WoSCC). The VOS viewer, and CiteSpace software were used to perform the bibliometric analysis. Publication language, annual growth trend, countries/regions and institutions, journals, keywords, references, and citation bursts were analyzed. Results: A total of 731 publications from 2011 to 2022 were retrieved. Annual publication records grew from two to more than 100 during this period. China had the highest number of publications (n=326). Sixty-five keywords that appeared more than four times were classified into six clusters: femtosecond laser technology, dry eye, biomechanics, visual quality, complications, and hyperopia. Conclusion: The number of literatures has been growing rapidly in the past 12 years. Our study provides a deep insight into publications on SMILE for researchers and clinicians with bibliometric analysis for the first time. Keywords: bibliometric analysis, small incision lenticule extraction, SMILE, femtosecond laser technology, complications